STUDI ASPEK PERMINTAAN MASYARAKAT TERHADAP PENYEWAAN AIRBNB DI KOTA BANDUNG PADA MASA PANDEMI COVID-19: STUDI KASUS MASYARAKAT GENERASI Z DOMISILI JABODETABEK - Farhan Firdaus, Muhammad
The COVID-19 pandemic has changed the world's economic order, through social distancing recommendations. This results in a lower level of demand for travel. The same is true for AirBnB, which is a digital-based platform with the concept of sharing economy and peer to peer accommodation. As a result of this pandemic, AirBnB suffered deep losses in almost all countries. Bandung is one of the cities in Indonesia with the highest number of AirBnB listings which have also experienced the negative impact of the COVID-19 pandemic. Before this pandemic occurred, AirBnB listings in Bandung were increasing every year with the majority of visitors coming from Jabodetabek. The majority of AirBnB visitors are generation Z youth due to their ability to access digital-based AirBnB. However, when the COVID-19 pandemic hit, the number of visitors decreased. Therefore this research will examine aspects of public demand for AirBnB in Bandung City during the COVID-19 pandemic using case studies of generation Z people who live in Jabodetabek. This research was conducted using questionnaire data for people who are interested in renting AirBnB in Bandung during the COVID-19 pandemic. The analysis used includes quantitative descriptive analysis to describe the characteristics and accommodation choices of potential customers, factor analysis to formulate the determinants of potential consumers, scoring analysis to formulate the order of the determining variables of potential consumers in choosing the type of accommodation, and hotspot analysis to determine the area cluster in Bandung City based on the level of demand for AirBnB. This research will produce a profile of potential AirBnB customers, the factors that determine them to rent AirBnB, the type of accommodation they are most interested in, and the location with high demand in Bandung City. The results of this study can be useful as a database for AirBnB to respond to the COVID-19 pandemic, because they already know the aspects of potential consumer demand for AirBnB during this pandemic.